Rock art and the contested landscape of the north eastern Cape, South Africa - Henry, Leila (My University, 2010)
ABSTRACT The north Eastern Cape is well known for its exceptional fine-line rock art. Recently, two non-fine-line traditions have been identified in the high mountains of this region. These corpora of rock art formed part of the interaction between San and non-San individuals in the creolised context of the nineteenth century. My discovery of further non-fine-line rock art, on the inland plateau, offers an opportunity to better understand the development of non-fine-line rock art and the role it played in relations between different groups. I argue that these three corpora of non-fine-line rock art are chronological variants of a single tradition, which I label the Type 2 tradition. The development of this tradition is associated with the breakdown of independent San-led bands and their loss of control of the space of painting, which became a contested landscape as multi-ethnic groups vied for political influence in the region and access to the San spirit world that would aid in their raiding prowess.